Hydroalcoholic extracts of Parkinsonia aculeata: a sustainable alternative for the biocontrol of Fusarium oxysporum - Argentel-Martínez, Leandris; Arvizu-Quintana, Eivy Fabiola; Peñuelas-Rubio, Ofelda; Leyva-Ponce, Aurelio; García-Urías, Julio (Renewable Energy, Biomass & Sustainability, 2021)
Fusarium, caused by Fusarium oxysporum Schlecht, generates significant losses in important crops in the Northwest Mexico, mainly in the State of Sonora. Given the need to reduce polluting loads due to the use of commercial fungicides, the use of sustainable ecological biotechnological alternatives such as plant extracts for disease biocontrol is a partial solution in both organic and traditional production systems. The present work aimed to evaluate the antifungal potential of hydroalcoholic extracts from leaves and stems of Parkinsonia aculeata L., Sp. Pl. (palo verde) for Fusarium oxysporum Schlecht biocontrol. Plant samples were taken from two semi-arid ecosystems (Bahía de Lobos, Site 1, and Tesopaco, Site 2). This samples were used to obtain and apply two volumes of hydroalcoholic extracts (300 and 500 ppm) in the culture medium prepared for the mycelial growth of Fusarium oxysporum Schlecht. As a control, distilled water was used to evaluate the free mycelial growth (dependent variable) and the commercial fungicide (TIABENDAZOL) for the total control of the fungus. These extracts were added to culture media using the poison culture medium technique. The treatments were placed in a growth chamber, following a completely randomized experimental design with a trifactorial arrangement. The extracts of Parkinsonia aculeata L., Sp. Pl. from both sites and volumes (300 ppm, and at 500 ppm) showed effectiveness for mycelial growth inhibition. There was a highly significant interaction between the three established factors. The source of variation with the greatest contribution to the total variability found was the volume in the culture medium. The minimum inhibitory volume of the hydroalcoholic extract was 289 ppm and the lethal least squared volume was 444 ppm in the culture medium. The obtained results confirm the viability of using hydroalcoholic extracts of Parkinsonia aculeata L., Sp. Pl.as a sustainable alternative for Fusarium oxysporum Schlecht biocontrol of in the agricultural production systems of northwestern Mexico.